#TITLE_ALTERNATIVE# - NUGROHO (NIM 22405010), HENDRO
One of the basic researches in earth science which requires to be conducted to assist the effort of mitigation of earthquake disaster is to determine the earthquake source (hypocenter) with high precision. In this case, carefulness is indeed needed because of the existence of heterogeneous earth’s interior passed by seismic wave from the hypocenter to a seismic station. Therefore, the use of tomography model (3D seismic velocity model) is expected to be able to help obtain a better hypocenter location of an earthquake. For this study, Java and its surroundings has been taken as the study area i.e., 7° S-11° S and 105° E-114° E. The data used in this study is arrival time of P wave from seismogram recorded at seismographic broadband stations in Indonesia. The determination of hypocenter used a method of guided grid search with the 3D velocity model resulting from tomographic imaging of the Sunda arc. Results of the determination of earthquake hypocenter with this approach provide smaller residual time errors compared to those resulting from the use of 1D velocity model.